2015
DOI: 10.1016/j.gene.2015.07.066
|View full text |Cite
|
Sign up to set email alerts
|

KAEA (SUDPRO), a member of the ubiquitous KEOPS/EKC protein complex, regulates the arginine catabolic pathway and the expression of several other genes in Aspergillus nidulans

Abstract: The kaeA(KAE1) (suDpro) gene, which was identified in Aspergillus nidulans as a suppressor of proline auxotrophic mutations, encodes the orthologue of Saccharomyces cerevisiae Kae1p, a member of the evolutionarily conserved KEOPS/EKC (Kinase, Endopeptidase and Other Proteins of Small size/Endopeptidase-like and Kinase associated to transcribed Chromatin) complex. In yeast, this complex has been shown to be involved in tRNA modification, transcription, and genome maintenance. In A. nidulans, mutations in kaeA r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 101 publications
0
11
0
1
Order By: Relevance
“…Although S. cerevisiae kae1Δ strains are viable, they have severe growth defects and pleiotropic phenotypes 4,18 and this is also the case in another fungus, Aspergillus nidulans. 36 In the human malaria parasite Plasmodium falciparum, the cytoplasmic KAE1 gene appears to be essential. 37 Recent studies have shown that the absence of KAE1 also leads to strong phenotypes in multicellular organisms, such tissue-specific cell growth regulated by t 6 A in flies.…”
Section: Discussionmentioning
confidence: 99%
“…Although S. cerevisiae kae1Δ strains are viable, they have severe growth defects and pleiotropic phenotypes 4,18 and this is also the case in another fungus, Aspergillus nidulans. 36 In the human malaria parasite Plasmodium falciparum, the cytoplasmic KAE1 gene appears to be essential. 37 Recent studies have shown that the absence of KAE1 also leads to strong phenotypes in multicellular organisms, such tissue-specific cell growth regulated by t 6 A in flies.…”
Section: Discussionmentioning
confidence: 99%
“…In the model filamentous fungus Aspergillus nidulans , mutations in the kaeA gene (previously called suDpro ) were identified as suppressors of proline auxotrophic ( pro − ) mutations [ 20 ]. Two characterized kaeA mutations (previously called suD19pro and suD25pro ) result in upregulation of agaA and otaA genes, coding for arginine catabolic enzymes: arginase and ornithine aminotransferase, respectively [ 21 , 22 ]. Both of these mutations are short deletions in the kaeA coding region, which do not change the reading frame.…”
Section: Introductionmentioning
confidence: 99%
“…These mutations do not change the sequence of the conserved regions of the protein. A model of the KaeA structure shows that amino acids from both deleted regions are localized on the protein surface, and it has been proposed that these deletions influence the interaction of KaeA with KEOPS subunits or other proteins [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Egy új tanulmány szerint, A. nidulans-ban a KEOPS/EKC komplex egyik tagja több olyan különböző metabolikus útvonal szabályozásában is részt vesz (Dzikowska és mtsi., 2015), amely útvonalak Candida fajokban összefüggésbe hozhatóak a patogenitás kialakulásával. Ezért a komplex egyes tagjai bizonyos fajok fertőzőképességét is befolyásolhatják.…”
Section: A Cpar2_303700 δ/δ Mutáns Törzs In Vivo Virulencia Vizsgálataunclassified